More sugar, less tea - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
In Mauritius, sugar cane plantations are gradually replacing tea plantations, for two simple reasons. Firstly, the quality of Mauritian tea does not compete well in the international market and secondly, the sugar industry has not yet filled the...